(untitled) (Research, Society and Development, 2021)
The interrelation between Periodontal Disease (PD) and Renal Insufficiency Chronic (RIC) is unavoidable, as patients with RIC have intrabuccal characteristics that predispose and / or aggravate PD such as: xerostomia, periodontitis, bone resorption, dental calculus and large accumulation of dental biofilm. The aim of this study was to assess the prevalence of PD in patients with RIC admitted to a public ICU in Manaus / AM. All in patients who had at least 6 teeth, one per sextant, were eligible to participate in this study. The Simplified Periodontal Examination was performed by measuring the depth of the probe to detect the periodontal pocket at 3 sites: mediovestibular, mesiovestibular and distovestibular. Of the 30 patients included in the analysis, 63.3% were male, twenty-eight (93.3%) had periodontal disease, while only two (6.7%) had a healthy periodontium. A generalized form of periodontitis was seen in 21 patients (75%). And taking into account the severity of periodontitis, only 8 of the patients (28.6%) had a mild degree of the disease. It was concluded that, in this sample, the prevalence of PD in patients with RIC admitted to the ICU is high, with a predominance of a generalized form of periodontitis. Thus, RIC does not seem to be in itself the only triggering factor for the high mortality rates that affect patients admitted to the ICU, which proves the importance and need of the dentist in a multidisciplinary team in a hospital environment.